The Effect of Time and Place Dimensions on Changing the Quality Dimensions of Sizes of Cities: A Case Study (Baghdad city) - ابراهيم, م.م.نسرين رزاق (Journal of Planner and Development, 2012)
The city has normal natural state, and the man has a usual movement, change and search for the new .Also, the city has a usual change and transform in its time, place and quality (sizes)structures. The city has a solid memory diving into the past and the future and reflects The real present, and this memory has a timing layers change into real materialistic place making the city has accumulated overlapping circles which is hard to break u , and it broadcasts the lockup timing density ,in which there is no visual record precisely, it is just like((the social record)) that evaluates the un visual relationships between the components and parts of the city (community and form) in a visual quiet exhibition and transform change inside. There is no city on earth stayed as it is in its size and shape, in which both of these are in a continuous change (increase and decrease) and continuous transform. Because all cities lie on urbanization development pressures that is the population growth and become exhibited worldly especially after the Second World War. Thus, the problem lies on the defect of time and place structures of the city that reflects negatively on the quality structures (sizes). Then, the deformed change and growth of the city loses its historical storage and it imitates the growth samples out of it is contexts that can not follow it. The cities are born as an urban organization which it could be formal or communal, and it don’t stay on its size or form which it born upon them. Actually it's suffer from transformation and changing's or both of them and they are caused by the effects of time and place. As a result of these effects the city may be witness (size operation), or change its architectural properties, all this will be study in the theoretical side of the research. The research applied its theory on Baghdad city as a case study. Baghdad so that any other cities as something alive which is born, then witness transformations and changing which causing to it time and place effects, they are effect its size (increase and decrease) according to the time effect (event) that made the change or the place effect, and all above will be search in more details with a historical sequences, and in a descriptive and analytical method during the practical side of the research. For this, the research aims at checking these effects of time and place and its reflection on the quality size of city (area and population) taking the change in size of Baghdad city and its growth through the